2017
DOI: 10.1016/j.jdermsci.2017.03.011
|View full text |Cite
|
Sign up to set email alerts
|

Anti-melanogenic activity of phytosphingosine via the modulation of the microphthalmia-associated transcription factor signaling pathway

Abstract: The modulation of MITF by phytosphingosine is closely related with the signaling pathways, such as the suppression of the MITF gene expression and the degradation of the MITF protein, depending on the duration of treatment time. These results suggest that phytosphingosine might serve as an effective melanogenesis inhibitor in melanocytes via the regulation of the MITF signaling pathways.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
16
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 26 publications
(17 citation statements)
references
References 43 publications
1
16
0
Order By: Relevance
“…We propose two plausible hypothesis. First, NAT10 may act as a transcriptional activator of MITF promoter alone or in cooperation with several transcription factors, including cAMP response element-binding protein (CREB), paired box 3 (PAX3), SRY-related HMG-box 10 (SOX10), and lymphoid enhancing factor-1 (LEF-1), which are known as upstream transcription regulators of MITF [ 17 ]. Alternatively, NAT10 may regulate post-translational modification such as N -terminal acetylation of MITF or its upstream transcription regulators.…”
Section: Discussionmentioning
confidence: 99%
“…We propose two plausible hypothesis. First, NAT10 may act as a transcriptional activator of MITF promoter alone or in cooperation with several transcription factors, including cAMP response element-binding protein (CREB), paired box 3 (PAX3), SRY-related HMG-box 10 (SOX10), and lymphoid enhancing factor-1 (LEF-1), which are known as upstream transcription regulators of MITF [ 17 ]. Alternatively, NAT10 may regulate post-translational modification such as N -terminal acetylation of MITF or its upstream transcription regulators.…”
Section: Discussionmentioning
confidence: 99%
“…It is responsible for the regulation of key genes for melanocyte development and differentiation [48]. It was found that the suppression of the MITF gene expression and degradation of the MITF protein or negatively regulation of its stability inhibited melanin synthesis [49,50].…”
Section: Discussionmentioning
confidence: 99%
“…When the levels of TRP-1 and TRP-2 were increased by up-regulated expression of MITF, the expression of tyrosinase was promoted and the melanogenesis-related enzymes produced melanin [18,32]. The expression of melanogenesis-mediated proteins was observed using western blotting to determine the anti-melanogenic effect of EU extract and fractions in B16-F10 melanoma cells.…”
Section: Discussionmentioning
confidence: 99%